2010
DOI: 10.1098/rspb.2010.0179
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, niche conservatism and the latitudinal diversity gradient in mammals

Abstract: Biologists have long searched for mechanisms responsible for the increase in species richness with decreasing latitude. The strong correlation between species richness and climate is frequently interpreted as reflecting a causal link via processes linked to energy or evolutionary rates. Here, we investigate how the aggregation of clades, as dictated by phylogeny, can give rise to significant climate-richness gradients without gradients in diversification or environmental carrying capacity. The relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
310
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(333 citation statements)
references
References 52 publications
19
310
4
Order By: Relevance
“…According to these hypotheses, we would expect to find an evolutionary trend consisting of lineages producing descendants that shift towards lower latitudes more frequently than the opposite. However, trends can be much more complex than that, as it has been shown that patterns can vary among groups and through time [53,66]. Given that our results suggest that differences in diversification rates might not have played a key role in the generation of the latitudinal gradient, it seems that further research on the dynamics of dispersal through time, and not only on diversification trends, will be necessary to fully understand the factors that shaped the spatial distribution of diversity in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…According to these hypotheses, we would expect to find an evolutionary trend consisting of lineages producing descendants that shift towards lower latitudes more frequently than the opposite. However, trends can be much more complex than that, as it has been shown that patterns can vary among groups and through time [53,66]. Given that our results suggest that differences in diversification rates might not have played a key role in the generation of the latitudinal gradient, it seems that further research on the dynamics of dispersal through time, and not only on diversification trends, will be necessary to fully understand the factors that shaped the spatial distribution of diversity in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this is probably an underestimate because: (1) the peak species richness in the Cenozoic may well have been higher than today's richness, based on their Cenozoic diversity trajectory 12 ; (2) it appears that the biome today that has the highest species richness (that is, the tropical moist forests 17 ) has shrunk considerably in the past dozen Myr 18 , which further supports the idea that the diversity of mammals may have been higher in the early to mid Miocene 12 (15)(16)(17)(18)(19)(20)(21)(22)(23) Myr ago) than today.…”
Section: The Second Law Of Palaeobiologymentioning
confidence: 99%
“…Quantifying niche relationships between related and/or partly sympatric species is of fundamental interest in ecology, since they provide a solid basis for further experimental or observational work and raise questions about mechanistic underpinnings of broad-scale biogeographic patterns (Buckley et al 2010;Peterson et al 1999). The application of newly developed techniques (e.g., Warren et al 2008) for inferring the divergence between Procapra species found strong interspecific variation in the observed environmental niches.…”
Section: Niche Divergencementioning
confidence: 99%